PENGARUH TERPAAN BERITA PASCA KRISIS DAN TERPAAN KONTEN INSTAGRAM @GARUDA.INDONESIA TERHADAP TINGKAT KEPERCAYAAN PADA GARUDA INDONESIA - Tazki Valeda, Delicia; Surayya Ulfa, Nurist (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research is driven by the post-crisis situation of Garuda Indonesia, the state-owned national airline that is still striving to rebuild public trust following a series of challenges, including financial losses, mounting debts, instances of corruption and mismanagement. The restoration of trust has been accompanied by a variety of post-crisis news coverage in the mass media over the past year. In order to compensate for the frequency with which it is reported on, Garuda Indonesia has begun uploading content to its Instagram account with the aim of increasing public trust. The objective of this study is to ascertain the impact of post-crisis news exposure and exposure to @garuda.indonesia Instagram content on the level of trust in Garuda Indonesia. This research is of an explanatory quantitative research. The sampling technique employed was non-probability sampling, with the target population comprising Indonesian individuals who were aware of Garuda Indonesia's post-crisis news and had encountered the airline's Instagram content within the previous six months. Tests were conducted using linear regression analysis. The results demonstrated that news exposure exerted no partial effect on the level of trust, while content exposure exhibited a partially significant effect on the level of trust. Furthermore, the simultaneous exposure to both news and content had no effect on the level of trust.